Factorial models of rosenberg⇔s self-esteem scale in peruvian adolescents [Modelos factoriales de la Escala de Autoestima de Rosenberg en adolescentes peruanos] - Sánchez-Villena, Andy Rick (2021)
ABSTRACT The Rosenberg Self-Esteem Scale (RSE) is an instrument widely used and designed to measure self-esteem in a single dimension. The aim of this research was to analyze the internal structure and the reliability of the RSE in Peruvian adolescents. The scale was administered to a total of 715 adolescents (51.3% female) with an average age of 12.20 years. Six models were identified by confirmatory factor analysis, which correspond to factorial structures reported in previous studies. The results showed a better goodness of fit for the one-dimensional model with control of method effects on inverse items, eliminating item 8 due to its ambiguity. Reliability was adequate and was calculated using the omega coefficient. The unifactorial structure of the RSE is discussed and it is concluded that the instrument reports evidence of validity and adequate internal consistency to be used in the Peruvian context.